Strategi Memperkuat Eksistensi Pendidikan Islam di Era Industri 4.0 dan Society 5.0 - Abdul Aziz (STKIP PGRI SITUBONDO, 2023)
The era of the Industrial Revolution 4.0 is an era demanding a rapid change. It is marked by the cyber-physical systems, cloud computing, and the Internet of Things (IoT), all relate to artificial intelligence and big data. In this digital era, technological advances have offered many conveniences for humans. One of them is a development of the online industry, online tutoring and online facilities such as e-books, online learning videos, learning applications, practice questions, discussions, and online study consultations. From this problem, this article focused on how the response of Islamic religious education teachers in facing the development of the industry? How is the strategy of Islamic education to exist and be consistent in the era of society 5.0? This study aimed to determine the readiness of Islamic religious education teachers in facing the industry and obtain the right strategy in maintaining the Islamic religious education in the era of industry 4.0 and society 5.0. This article used a literature study method, where data was obtained from various books and literature, documents, journals, articles and information from other print and electronic media related to the problems observed. After collecting data, collecting, and grouping, discussion and analysis were carried out. The results of this study; First, insufficient human resources. Second, many teachers are old. Third, the infrastructure is not perfect. Fourth, the method of teaching Islam is carried out in a particular tradition. Strategies to maintain Islamic Education, namely, 1) teachers must be able to take advantage of existing technological facilities. 2) Islamic educational institutions must be able to improve human resources. 3) modernization is necessary for reforming the Islamic education system, starting from the paradigm, conceptual framework and evaluation. 4) Islamic educational institutions, as the driving force, must be high quality